2020
DOI: 10.1080/23802359.2019.1710284
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome ofAnnamanum lunulatum(Coleoptera: Lamiinae) and its phylogeny

Abstract: 2020) The complete mitochondrial genome of Annamanum lunulatum (Coleoptera: Lamiinae) and its phylogeny, Mitochondrial DNA Part B, 5:1, 551-553, ABSTRACTThe complete mitochondrial genome of the Annamanum lunulatum is 15,610 bp in length, which contains 13 protein-coding genes, 22 transfer RNAs, two ribosomal RNAs, and the A þ T-rich region. The arrangement of genes is identical to all know longhorn beetles mitochondrial genomes. The overall AT content of the mitochondrial genome is 75.3%, whereas the AT conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…The Lamiinae subfamily is widely distributed and contains the largest number of species among the Cerambycidae, but the phylogenetic relationships within Lamiinae are still controversial [ 2 ]. However, the subfamily is considered to be a monophyletic group, as has been shown in previous studies [ 2 , 9 , 10 , 11 ]. In our study, two species within the subfamily Entiminae were selected as the outgroups, and the results showed that all the Lamiinae species were well separated with a high degree of confidence.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The Lamiinae subfamily is widely distributed and contains the largest number of species among the Cerambycidae, but the phylogenetic relationships within Lamiinae are still controversial [ 2 ]. However, the subfamily is considered to be a monophyletic group, as has been shown in previous studies [ 2 , 9 , 10 , 11 ]. In our study, two species within the subfamily Entiminae were selected as the outgroups, and the results showed that all the Lamiinae species were well separated with a high degree of confidence.…”
Section: Discussionmentioning
confidence: 94%
“…All mitochondrial genome sequences were manually proofread and spliced using DNASTAR Package v.6.0 software [ 43 ] and tRNA gene annotation was completed through the online website MITOS ( , accessed on 15 January 2021) [ 44 ]. The complete sequences of some Cerambycidae species were obtained from the GenBank database [ 1 , 2 , 11 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], and homologous sequence alignments were performed by the Clustal W program of Mega 7.0 [ 38 ] to determine the positions of the two rRNA genes and the AT-rich region. The four mitogenomes were deposited in GenBank with the accession numbers MW858148, MW858150-MW858152.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 2019a , 2019b , 2019c , Dai et al. 2020 ; Li and Lu 2020 ; Lin et al. 2020 ; Su and Wang 2020 ; Yan et al.…”
mentioning
confidence: 99%
“…In order to determine phylogenetic relationships within Cerambycinae, we used 25 species including Z. fulguratus with 22 other species from Cerambycinae and one species each from Prioninae and Laminae subfamilies as outgroups (Wang, Lan, et al 2019;Dai et al 2020), all downloaded from NCBI. The nucleotide sequences of the 13 PCGs were aligned by multiple alignment using fast Fourier transform (MAFFT) (Katoh and Standley 2013).…”
mentioning
confidence: 99%